Tarekat as Moral Formation: Reframing Religious Moderation through Moral Theology in North Sumatra - Abrar M. Dawud Faza; Intan Kumalasari; Sidiq Hartono (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2026)
This study critically examines the role of Tarekat (Ṣūfī orders) in fostering religious moderation within the socio-cultural plurality of North Sumatera. Employing a qualitative approach grounded in in-depth interviews, the research explores how spiritual teachings and embodied practices of the Tarekat shape moral dispositions that encourage tolerance, social harmony, and inclusive coexistence. Unlike previous sociological studies on Tarekat that primarily emphasize their social and cultural functions, this article examines Tarekat as a process of moral formation that generates communal virtues supportive of religious moderation. The findings demonstrate that core spiritual principles such as self-purification (tazkiyat al-nafs), disciplined self-control, and sustained attentiveness to God function as ethical resources that mitigate tendencies toward religious extremism among adherents. Beyond individual moral formation, tarekat communities actively engage in interreligious dialogue, mediate religious tensions, and promote inclusive participation in broader social life. From the perspective of moral theology, these practices illustrate how spiritually grounded ethical formation can contribute to the cultivation of communal virtues necessary for pluralistic societies. The study argues that Tarekat not only serve as loci of spiritual devotion but also operate as morally significant agents of religious moderation, offering a constructive model for sustaining social harmony in contexts marked by religious and cultural diversity.